Media education in Mexico: vulnerability and risk among social network users - Aguirre Aguilar, Genaro (2019)
The fragility and vulnerability caused by some practices and habits in the face of media consumption and the use of technologies by Mexicans lead to discuss the absence of educational policies aimed at media education and digital literacy: an issue that has historically been pending in the public agenda and among academic communities in the past few years. This article starts from an experience lived in the state of Veracruz, which triggered a series of events unveiling the vulnerability in the consumption and use of ICTs that affects its citizens. Thus, some theoretical aspects that contribute to seize the importance of media education and the responsible use of technologies in a country like Mexico are recovered, since events related to such experience still occur nowadays with poor results.